Reasons for the Use of Health Care in Elderly Persons Undergoing Consultation in the University Clinic of Internal Medicine and Medical Oncology of the Hubert Koutoukou Maga National Hospital and University Center (CNHU-HKM) of Cotonou - Azon-Kouanou, Angèle; Aïdasso, Mahougnon Jean-Christ Alix; Missiho, Mahoutin Semassa Ghislain; Dansou, Jean; Karuhije, Faustin Havugimana; Kondoli, Janvier Kitumaini; OBA, Richard; Agbodande, K.A.; Sokadjo, Yves Morel; Zannou, Djimon Marcel; HOUNGBE, FABIEN (My University, 2020)
Introduction: The progressive ageing of the population from southern Sahara is leading to an increase in health needs among the elderly. The purpose of this study was to output an overview about the reasons why the elderly come for consultation in the internal medicine department of the HKM-NHUC in Cotonou. Methodology: This was a retrospective, descriptive, and analytical study, which included all patients aged 65 years and over, who came for the first time for consultation in the Internal Medicine Department of the CNHU- HKM between January 1st and December 31st, 2017. Results: Among the 680 new patients received in internal Medicine consultations during the study period, 118 people were aged 65 and over, representing a hospital frequency of 17.35%. The sex ratio was 0.9 with a mean age of 73 ± 7 years. Hypertension was the main comorbidity of the patients (69%). Cough (11.3%) and low back pain (8.2%) dominated the reasons for consultation. The three main noso- logical groups of pathologies were, in descending order, diseases of the osteo- articular system (17.5%), diseases of the respiratory system (16.5%) and dis- eases of the circulatory system (12.4%). Pneumonia (11.3%) and lumbosacral spondylarthrosis (10.3%) were the most frequent pathologies in patients whose health needs remain quite varied. Conclusion: The elderly become gradually an important part of the population in southern Sahara. A better understanding of the health needs of this category of the population is necessary to deal effectively with the health challenges that will accompany this phenomenon.
Keywords: The Elderly; Reason for Consultation; Internal Medicine